Assessing The Impact Of Surgical Approaches On Total HIP Replace-ment Outcomes: A Systematic Review - Andriessanto C. Lengkong; Rangga B.V Rawung; Stefan A.G.P Kambey (Green Publisher Indonesia, 2024)
Total hip replacement is one of the most common and effective orthopedic surgical procedures to reduce pain and improve hip function in patients with severe conditions. This procedure has undergone many advances in the past few decades. However, there is debate among surgeons about which surgical approach is the most optimal to apply. This study aims to systematically assess and compare the outcomes of different surgical approaches in total hip replacement (THR) procedures. The method used in this study was a systematic literature review, in which literature was searched through academic databases such as PubMed, Scopus, and Google Scholar using relevant keywords. The collected data were then analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results of this study show that each surgical method for total hip replacement has different advantages and disadvantages. The choice of surgical approach should be tailored to each patient's specific condition. Based on a review of the available literature, the anterior approach is often considered superior to the other approaches. The advantages include less surgical trauma, better postoperative pain reduction and a faster rehabilitation process. The anterior approach is considered safe, reliable and effective, and results in lower pain levels compared to other methods